1999
DOI: 10.1101/gr.9.10.960
|View full text |Cite
|
Sign up to set email alerts
|

Generation and Analysis of 25 Mb of Genomic DNA from the Pufferfish Fugu rubripes by Sequence Scanning

Abstract: We have generated and analyzed >50,000 shotgun clones from 1059 Fugu cosmid clones. All sequences have been minimally edited and searched against protein and DNA databases. These data are all displayed on a searchable, publicly available web site at http://fugu.hgmp.mrc.ac.uk/. With an average of 50 reads per cosmid, this is virtually nonredundant sequence skimming, covering 30%-50% of each clone. This essentially random data set covers nearly 25 Mb (>6%) of the Fugu genome and forms the basis of a series of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
52
1

Year Published

2000
2000
2005
2005

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(56 citation statements)
references
References 38 publications
(43 reference statements)
3
52
1
Order By: Relevance
“…7, which is published as supplemental data on the PNAS web site, www.pnas.org). These data are consistent with previous observations that, in at least some regions of the genome, pufferfish speciation has been accompanied by particularly high rates of chromosomal rearrangements (61)(62)(63)(64). It is possible that genome compression in the pufferfish has been achieved, at least in part, by clustering together genes with shared domains of expression.…”
Section: Expression Of the Pufferfish Scl Gene In Transgenic Zebrafishsupporting
confidence: 81%
“…7, which is published as supplemental data on the PNAS web site, www.pnas.org). These data are consistent with previous observations that, in at least some regions of the genome, pufferfish speciation has been accompanied by particularly high rates of chromosomal rearrangements (61)(62)(63)(64). It is possible that genome compression in the pufferfish has been achieved, at least in part, by clustering together genes with shared domains of expression.…”
Section: Expression Of the Pufferfish Scl Gene In Transgenic Zebrafishsupporting
confidence: 81%
“…During routine Fugu cosmid library sequence scanning (within the confines of the Fugu Landmark Mapping Project (Elgar et al 1999)) a cosmid (C139D21) was identified as having a gene fragment with high sequence similarity to goldfish VPAC 1 R (probability value in excess of 9e -19 ). PCR primers were designed for a conserved sequence motif of this family identified after a multiple sequence alignment of all the members of this family and the Fugu cosmid C139D21 partial sequence.…”
Section: Gene Identification and Isolationmentioning
confidence: 99%
“…For example, Morizot et al (1991) have estimated that the genome of the platyfish (genus Xiphophorus) is five times smaller than the human genome. Elgar et al (1999) estimated that the pufferfish genome is eight times smaller than the human genome and suggested that the duplication of Hox clusters by regional duplication is easier to reconcile with fish genome size data than a complete genome duplication. However, the small genome of Fugu may be due to the reduction of intergenic and noncoding regions (Venkatesh et al 2000).…”
Section: Introductionmentioning
confidence: 99%